Autonomic dysfunction and risk of severe hypoglycemia among individuals with type 2 diabetes - Arnaud D. Kaze; Matthew F. Yuyun; Rexford S. Ahima; Michael R. Rickels; Justin B. Echouffo-Tcheugui (JCI Insight, 2022)
There are limited data on the link between cardiac autonomic neuropathy (CAN) and severe hypoglycemia in type 2 diabetes. Here, we evaluated the associations of CAN with severe hypoglycemia among 7,421 adults with type 2 diabetes from the Action to Control Cardiovascular Risk in Diabetes study. CAN was defined using ECG-derived measures. Cox’s and Andersen-Gill regression models were used to generate HRs (HRs) for the first and recurrent severe hypoglycemic episodes, respectively. Over 4.7 years, there were 558 first and 811 recurrent hypoglycemic events. Participants with CAN had increased risks of a first episode or recurrent episodes of severe hypoglycemia. The intensity of glycemic management modified the CAN association with hypoglycemia. In the standard glycemic management group, compared with those of participants without CAN, HRs for a first severe hypoglycemia event and recurrent hypoglycemia were 1.58 and 1.96, respectively. In the intensive glycemic management group, HRs for a first severe hypoglycemia event and recurrent hypoglycemia were 1.10 and 1.24, respectively. In summary, CAN was independently associated with higher risks of a first hypoglycemia event and recurrent hypoglycemia among adults with type 2 diabetes, with the highest risk observed among those on standard glycemic management.